Miscarriage and early first trimester growth restriction by ultrasound - Agarwal, Neelima; Sharma, Amita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Concern about the possibility of spontaneous miscarriage is one of the most common reasons women seek evaluation in the emergency department during their first trimester. According to the obstetrics and gynecology literature, it is estimated that 20% to 25% of all clinically recognized pregnancies result in spontaneous miscarriage. The objective of the study is to examine with whether viable early pregnancies that subsequently end in miscarriage exhibit evidence of first-trimester growth restriction. The prospective cohort study design used for this purpose with setting of Antenatal clinic of a teaching hospital. Women attending the clinic between 5 and 10 weeks of gestation took part in the study. Methods: Women with spontaneously conceived intrauterine, viable singleton pregnancies with certain last menstrual period and regular cycles were included. The deviation between the observed and expected crown-rump length (CRL) for gestation was calculated and expressed as a z-score. Pregnancies were followed up until 11-14 weeks, and the deviation between those that remained viable and miscarried subsequently was calculated. Viability at 11-14 weeks was measured. Results: Over 12 months, 320 women met the inclusion criteria. Twenty women were excluded. Of the remaining 300, the pregnancy remained viable in 248 (82.6%) and 52 (17.4%) suffered a miscarriage. At the first transvaginal ultrasound, the z score of the mean measured CRL for pregnancies that remained viable was -0.69 while in pregnancies that subsequently miscarried the z-score was -2.95 and the CRL was significantly smaller (P < 0.048). In the latter group, the initial CRL was below the expected mean for gestational age in all women. Conclusions: CRL was significantly smaller in pregnancies that subsequently ended in miscarriage. This suggests that early first trimester growth restriction is associated with subsequent intrauterine death.